Recent Advancements in Battery Management System for Li‐Ion Batteries of Electric Vehicles: Future Role of Digital Twin, Cyber‐Physical Systems, Battery Swapping Technology, and Nondestructive Testing. Issue 8 (26th June 2021) - Panwar, Nitika G.; Singh, Surinder; Garg, Akhil; Gupta, Abhishek Kumar; Gao, Liang
Abstract : The increasing popularity of the electric vehicles (EVs) is due to various environmental impacts of the gasoline‐/diesel‐based vehicles over the past few decades. EVs are commercialized in various parts of world but their full‐scale commercialization has not yet attained. Despite of many advantages, challenges associated with the use of EVs are their range anxiety, slow charging, and the performance/cost of battery. A thorough review from the year 2006 to 2020 is conducted in the field of battery management system (BMS). Herein, various functions, advantages, and disadvantages of methods used in BMS for cell balancing, thermal management, and protection of battery against over‐voltage and over current, estimation of state of health, and estimation of state of charge of battery are discussed. Additionally, critical gaps are identified and a framework for design of an efficient BMS is proposed. The deployment of advanced intelligent and smart technologies such as digital‐twin of battery pack, cyber‐physical systems, battery swapping technology, nondestructive testing, self‐reconfigurable batteries, and prudent recycling/reusability using automation are also discussed. In‐brief, critical gaps; advanced technologies and framework that researchers can use to develop comprehensive systems comprising advanced BMS; real‐time battery monitoring, and battery reusability and recycling; as a whole complete unit are provided. Abstract : The development of a digital twin of a battery requires a coherent integration of artificial intelligence (AI), Internet of things (IoT), big data in cloud computing, and cyber‐physical systems (CPSs). CPS comprises sensors, microprocessors, WIFI, wireless sensors, and the essential hardware for estimating, evaluating, simulating, and optimizing the battery performance in real time.